Review (Modern theology, 1993)
Book reviewed in this article: Church of Churches. The Ecclesiology of Communion, by J.-M.R. Tillard, O.P.tr the Church, Community of Salvation. An Ecumenical Ecclesdiology (New Theology Studies 1) by George H.Tavard. Rome and the Eastern Churches. A study in schism, by Aidan Nichols, O.P. Liberating Reformed theology: A South African Contribution to en Ecumencial Debate, by John W.de Gruchy, Grand Rapids Persons, Divine and Human, eds. Chridtoph Schwobel and Colin E.Gunton